Beberapa Faktor Risiko yang Berhubungan dengan Kejadian Tuberkulosis pada Anak di Puskesmas Kedungmundu Tahun 2025 - Khofifah Indah Nur Khoiriyah; Roro Kushartanti; Nur Gilang F (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2025)
Tuberculosis remains a global health problem. Based on WHO (World Health Organization) data, Indonesia is the country with the second highest number of TB sufferers in the world. Tuberculosis is transmitted rapidly through the air when an active Tuberculosis sufferer sneezes or coughs. Children are a vulnerable group, especially if there are risk factors around the child. The purpose of this study was to determine the risk factors associated with the incidence of tuberculosis in children at the Kedungmundu Community Health Center. The research method used was analytical observation with a Cross Sectional approach. The sample used in this study was 40 respondents. Data processing and analysis used univariate and bivariate analysis with Chi Square statistical tests using SPSS. The results showed that there was a relationship between contact history (p <0.001), residential density (p <0.001), parental knowledge (p = 0.025) and smoking history (p = 0.025) with the incidence of childhood tuberculosis. In addition, there was no relationship between age (p = 0.111), nutritional status (p = 1.000), immunization status, economic status (p = 0.361), and ventilation (p = 0.152) with the incidence of childhood tuberculosis. The conclusion of this study is that there is a significant relationship between contact history, residential density, parental knowledge and smoking history with the incidence of childhood tuberculosis at the Kedungmundu Community Health Center, Semarang City.